1950
DOI: 10.1071/ar9500144
|View full text |Cite
|
Sign up to set email alerts
|

Yellow dwarf of tobacco in Australia. V. Transmission by Orosius argentatus (Evans) to some alternative host plants.

Abstract: Tobacco yellow dwarf virus disease was experimentally transmitted to 15 species of plants by the leafhopper, Orosius argentatus (Evans). Eight of these plants are summer annuals and seven are autumn-spring growing plants which provide a continuous succession and wide range of hosts. Their occurrence in the districts where tobacco is grown makes control by the elimination of alternative host plants appear impracticable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Furthermore, this has been restricted to selected crops including lucerne (Helson 1951; Pilkington et al. 2004b), tomato (Osmelak 1986; Osmelak & Fletcher 1988) and tobacco (Hill 1941; Helson 1942, 1950; Hill & Helson 1949; Trębicki et al . 2009) with most studies targeting a single leafhopper species, particularly O. orientalis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this has been restricted to selected crops including lucerne (Helson 1951; Pilkington et al. 2004b), tomato (Osmelak 1986; Osmelak & Fletcher 1988) and tobacco (Hill 1941; Helson 1942, 1950; Hill & Helson 1949; Trębicki et al . 2009) with most studies targeting a single leafhopper species, particularly O. orientalis.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of TbYDV-infected A. retroflexus and R. raphanistrum in this study supports the notion that these weeds may act as reservoirs for virus acquisition by O. orientalis. However, tobacco is not considered to act as a virus reservoir because (a) no nymphal development and only limited adult survival has been recorded on N. tabacum (Hill, 1941;Helson, 1942) and (b) TbYDV transmission and acquisition studies have shown that O. orientalis cannot acquire the virus from TbYDV-infected tobacco (Helson, 1950). As such, tobacco should be considered a dead-end host for the virus as this plant species becomes infected only when the preferred leafhopper hosts decline and the insect is forced to feed on it.…”
Section: Discussionmentioning
confidence: 99%
“…Hill (1941) and later Helson (1950) reported that the leafhopper Orosius orientalis (Matsumura) (Hemiptera: Cicadellidae), previously described as O. argentatus (Evans) and Thamnotettix argentata (Evans), was a vector of the disease, but there has been little research aimed at identifying other potential vectors. Furthermore, although numerous host plants for TbYDV have been reported (Helson, 1950;Hill, 1950;Hill & Mandryk, 1954;Bowyer & Atherton, 1971), most of these have been identified under experimental conditions by the development of typical yellow dwarf symptoms in tobacco (Hill, 1937) following transmission from suspected host plants by either grafting or the vector O. orientalis. Recently, a TbYDV-specific PCR test was developed (van Rijswijk et al, 2004) which was used to determine the variability within the genome of Australian TbYDV isolates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this discovery has implications for studies of disease transmission in Australia. O. argentatus has been cited as a vector for several phytoplasma‐associated diseases in Australia including tomato big bud (Hill ; Bowyer ; but see Pilkington et al ), tobacco yellow dwarf (Hill ; Helson , ), lucerne witches broom (Helson ), legume little leaf (Hutton & Grylls ), potato purple top wilt and pawpaw yellow crinkle (Grylls ; Padovan & Gibb ), Australian lucerne yellows (Pilkington et al ) and equivocally for Australian grapevine yellows (Beanland et al ) and strawberry lethal yellows (Streten et al ). It could be expected that vector studies in eastern Australia are focussed on O. argentatus although care needs to be taken to confirm the identity of any vectors, using COI gene sequencing if necessary, particularly because additional species, three described as new in this paper, are known from southern and eastern Australia.…”
Section: Taxonomymentioning
confidence: 99%